Adventures of ideas - Whitehead, Alfred North (The Macmillan company, 1933)
This is one of three books that Whitehead wrote “to express a way of understanding the nature of things” [vii]. The central thesis of the book is that social changes result from the confrontational interaction between forces of compulsion and those of aspiration and affirmed beliefs. The book is a classic on a whole range of ideas intrinsic to human civilization from a European perspective. Whitehead says that the goal of his inquiry is to demonstrate those factors in Western civilization which jointly constitute a new element in the history of culture.